Rancang Bangun Purwa Rupa Pembangkit Listrik Tenaga Panas Matahari Metode Mesin Stirling - Rieza Azhar; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Solar thermal energy is a renewable energy which is very large in the universe. Indonesia as a tropical country has a huge potential where almost all the islands in Indonesia has solar thermal radiation every year. One of utilization of solar heat is to use solar heat as a source of electrical energy. solar thermal power generation technology, one of which is use a stirling engine as a converter of solar thermal energy into kinetic energy. Then the kinetic energy is connected to a generator that can produce electrical energy. One important part in the generation of solar thermal energy with the stirling engine method is the solar thermal collector which is generally a parabolic shape. In this study, a parabolic collector was designed using TracePro simulation software. TracePro Software is able to simulate solar thermal energy by providing several parameters, then it will display the performance of a paraboilic dish collector against sunlight as well as the parameters needed in research. From the results of the simulation, it was found that the ability of the maximum parabolic collector with 40 Watt/m2 solar radiation input was able to focus solar radiation to 500 W. From the results of the manual calculation there was an error between the simulation and the manual calculation is 16,6 %. Thus the performance of the parabolic dish collector by 83,4 % (efficiency). Keywords: solar thermal, stirling engine, software TracePro, parbolic collector